ARSITEKTUR RELIGI PESTA TIWAH DAYAK NGAJU SEBAGAI DAYA TARIK WISATA BUDAYA DI KALIMANTAN TENGAH - Carlos Iban; Tuti Elfrida (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2017)
Title: The Religious Architecture of Tiwah Feast among Dayak Ngaju as Cultural Tourism Attractions in Central Kalimantan The belief to a transcendent space among Dayak Ngaju people, especially for Kaharingan believers in Central Kalimantan, leads to the Tiwah Feast, a secondary funeral ceremony to transmit the soul of the dead to a celestial realm called The Lewu Tatau. The Tiwah Feast manifests in many meaningfulness of sacred symbols. There are certain rules in the implementation, particularly on the physical symbols and its religious architectures. This article emphasize the uniqueness of the symbols on the religious architecture of Tiwah Feast, which has the potential to become tourist attraction in the development of cultural tourism products. Using qualitative methods, data obtained through in-depth interviews, participant observation, and documentation, in two different locations, in Tumbang Koling and Ramang Village. Sacred symbols on its religious architecture include Sapundu and Sandong. A sapundu manifests in the form of a human or animal figure, regarding to the personification of the ancestral spirit. It shows the way for the soul towards Lewu Tatau. Meanwhile, Sandong is a secondary burial coffin to put the ancestral bones. The construction and architecture should concern on foundation, size, height, carvings, and ornaments. This local wisdom is potential to be developed as a cultural tourism attraction. However, the sacredness of the Tiwah Feast must be maintained and preserved from cultural commercialization and commodification issues.